Design of 200 km/h Passenger-Coaches’ Bogie - Yun LIANG; Honglong JIA; Yingchun ZHANG; Cheng CHEN; Di SHA; Changxiu LYU; Yisong WANG (机车电传动)
Combined with the application characteristics of 200 km/h passenger car bogies, the selection and analysis of key components were carried out in detail. It was proposed that the 200 km/h passenger car bogies adopt the structure of unconnected sleeper beam and the mode of direct connection between bogie and car body. The frame strength test and dynamic calculation were completed and passed. The test results showed that the 200 km/h passenger car bogie could meet the requirements of different line conditions from 160 km/h to 250 km/h by adjusting the suspension parameters.